Longitudinal assessment of antibiotic resistance gene profiles in gut microbiomes of infants at risk of eczema - Loo, Evelyn Xiu Ling (2021)
Background: While there is increasing knowledge about the gut microbiome, the factors influencing and the significance of the gut resistome are still not well understood. Infant gut commensals risk transferring multidrug-resistant antibiotic resistance genes (ARGs) to pathogenic bacteria. The rapid spread of multidrug-resistant pathogenic bacteria is a worldwide public health concern. Better understanding of the naïve infant gut resistome may build the evidence base for antimicrobial stewardship in both humans and in the food industry. Given the high carriage rate of extended spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae in Asia, we aimed to evaluate community prevalence, dynamics, and longitudinal changes in antibiotic resistance gene (ARG) profiles and prevalence of ESBL-producing E. coli and K. pneumoniae in the intestinal microbiome of infants participating in the Growing Up in Singapore Towards Healthy Outcomes (GUSTO) study, a longitudinal cohort study of pregnant women and their infants. Methods: We analysed ARGs in the first year of life among 75 infants at risk of eczema who had stool samples collected at multiple timepoints using metagenomics. Results: The mean number of ARGs per infant increased with age. The most common ARGs identified confer resistance to aminoglycoside, beta-lactam, macrolide and tetracycline antibiotics; all infants harboured these antibiotic resistance genes at some point in the first year of life. Few ARGs persisted throughout the first year of life. Beta-lactam resistant Escherichia coli and Klebsiella pneumoniae were detected in 4 (5.3%) and 32 (42.7%) of subjects respectively. Conclusion: In this longitudinal cohort study of infants living in a region with high endemic antibacterial resistance, we demonstrate that majority of the infants harboured several antibiotic resistance genes in their gut and showed that the infant gut resistome is diverse and dynamic over the first year of life.